Research Brokers, Researcher Identities and Affective Performances: The Insider/Outsider Conundrum. Issue 2 (3rd April 2019) - Parashar, Swati
ABSTRACT: This paper reflects upon the role of brokers in facilitating research in conflict zones, which the researcher identifies as 'native' areas of research in the Global South. Researchers from the Global South, based in academic and research institutions in Western locations and having received funding from foreign agencies, conduct field research in conflict geographies which they maybe native to, or may have inhabited for long periods of time. Brokers facilitate research in these 'native' areas of research, leading to difficult encounters between the researcher, research subjects and brokers themselves. I analyze the intimate and uncomfortable affective encounters between researchers and research brokers from the Global South who share national or cultural identity, language and above all, spatial nativity and familiarity.